2020
DOI: 10.1242/jcs.243733
|View full text |Cite
|
Sign up to set email alerts
|

Osh6 requires Ist2 for localization to ER–PM contacts and efficient phosphatidylserine transport in budding yeast

Abstract: Osh6 and Osh7 are lipid transfer proteins (LTPs) that move phosphatidylserine (PS) from the endoplasmic reticulum (ER) to the plasma membrane (PM). High PS level at the PM is key for many cellular functions. Intriguingly, Osh6/7 localize to ER-PM contact sites, although they lack membrane-targeting motifs, in contrast to multidomain LTPs that both bridge membranes and convey lipids. We show that Osh6 localization to contact sites depends on its interaction with the cytosolic tail of the ER-PM tether Ist2, a ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…the β-barrel, is highly conserved but decorated by external elements that are poorly conserved and mainly correspond to insertions that are specific to each ORP/Osh subfamily. Furthermore, functional data suggest that the ORD of some ORP/Osh proteins interact with partners (Nissila et al., 2012; Pietrangelo and Ridgway, 2019; D’Ambrosio et al., 2020). Thus, variation in the ORD, in addition to conferring distinct ligand specificity, might offer specialized binding zones for specific partners but also enable the protein to associate with organelles in different ways.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…the β-barrel, is highly conserved but decorated by external elements that are poorly conserved and mainly correspond to insertions that are specific to each ORP/Osh subfamily. Furthermore, functional data suggest that the ORD of some ORP/Osh proteins interact with partners (Nissila et al., 2012; Pietrangelo and Ridgway, 2019; D’Ambrosio et al., 2020). Thus, variation in the ORD, in addition to conferring distinct ligand specificity, might offer specialized binding zones for specific partners but also enable the protein to associate with organelles in different ways.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Osh6/7p are cytosolic but also localize at ER-PM contact sites (Schulz et al., 2009; Maeda et al., 2013), although they are devoid of known membrane-targeting motifs like those of the more complex Osh proteins. Recently, we showed that Osh6p/7p reside in these contact sites by interacting with Ist2p (D’Ambrosio et al., 2020) (Figure 6D). This protein is a homologue of TMEM16 proteins, a family of Ca 2+ -activated lipid scramblases (Wolf et al., 2012; Brunner et al., 2014; Wolf et al., 2014) and one of the few proteins that stabilize ER-PM contacts in yeast (Manford et al., 2012; Collado et al., 2019; Hoffmann et al., 2019).…”
Section: Functional Role and Structural Features Of Osh Proteinsmentioning
confidence: 96%
“…Cho1p) that generates PS from CDP-DAG and serine at the ER (Tani and Kuge, 2014). Moreover, silencing Sac1p or limiting Osh6/7p activity has the same effect (D'Ambrosio et al, 2020). Thus, if PS/PI(4)P exchange are stopped, PS synthesis is repressed due to elevated PS levels at the ER.…”
Section: Interplay Between Ps/pi(4)p Exchange and Pip Metabolism At Tmentioning
confidence: 99%
“…Osh6/7p are cytosolic but also locate to ER-PM contact sites ( Schulz et al, 2009 ; Maeda et al, 2013 ). Recently, we showed that this is due to their interaction with the ER-residing Ist2p protein ( D’Ambrosio et al, 2020 ). Ist2p is a homolog of Ca 2+ -activated lipid scramblases ( Wolf et al, 2012 , 2014 ; Brunner et al, 2014 ) and contributes to scaffolding yeast ER-PM contacts ( Manford et al, 2012 ; Collado et al, 2019 ; Hoffmann et al, 2019 ).…”
Section: Ps/pi(4)p Exchangers Represent a New Class Of Heterotypic LImentioning
confidence: 99%
“…ORP/Oshp family members are capable of binding and transferring oxysterols, cholesterol, phosphoinositides-4-phosphate[PI(4)P], and Phosphoinositides. In yeast and mammals, ORPs/Oshs can transfer phospholipids such as phosphatidylserine in an exchange reaction with PI4P (D’Ambrosio et al., 2020; Maeda et al., 2013; Venditti et al., 2019). ORP/Oshp family members share two phenylalanines in an acid tract (FFAT) and can be targeted to the ER via integral membrane protein VAP (VAMP-associated protein).…”
mentioning
confidence: 99%